Caracterização de células T regulatórias no sangue materno, de cordão e placenta de mães diabéticas - Queiroz, Adriele Ataides de (2018)
Diabetes mellitus and a number of diseases are associated with changes in regulatory T cells (Treg) in peripheral blood. However, the immunological responses of pregnant women with diabetes remain partially understood and the effects of Treg cells in these patients have not been investigated yet. The present study characterized the expression of regulatory T cells and T cells expressing FAS (CD95) in maternal blood, umbilical cord blood and placenta of pregnant women with diabetes from 18 to 35 years of age. The pregnant women were divided according to the glycemic state in a non-diabetic group (ND, N = 20) and type 2 diabetes mellitus (DM-2; N = 20). Cell subsets were determined by flow cytometry. Compared to ND, DM-2 blood cells exhibited higher expression of CD25 +, Foxp3 +, CD4 + CD25 +, CD4 + Foxp3 + and CD25 + Foxp3 +, and umbilical cord blood cells had lower expression of CD25 +, CD4 + Foxp3 + and CD25 + Foxp3 +. In the placenta, the villous layer of the DM-2 group, there was a lower proportion of CD3 + cells and CD25 + cells, as well as the ratio of CD4 + Foxp3 + and CD25 + Foxp3 + and the placental extravilous layer contained lower CD4 + and CD25 + levels and an increase of CD4 + Foxp3 + cells. In the maternal blood of DM-2, the frequency of CD3 + CD95 + and CD3CD4 + cells expressing CD95 + was lower. In DM-2 umbilical cord blood, the CD3 + CD95 + rate was lower. In the placenta, the villous layer of the DM-2 group had a lower percentage of CD3 + CD95 + cells and CD3 + CD4 + cells expressing CD95 +, whereas the percentage of cells expressing CD3 + CD45RO + was lower in both layers of the placenta. The data suggest that hyperglycemia alters regulatory T cell phenotypes and FAS expression in memory T cells, which may compromise T cell apoptosis and probably immunoregulation and maternal-fetal tolerance.